Entrepreneurial Cambodia : Cambodia Policy Note - Ehst, Michael; Sak, Sambath; Sanchez Martin, Miguel Eduardo; Van Nguyen, Lan (World Bank, Washington, DC, 2018)
Entrepreneurship is multi-faceted, with a range of factors influencing the success of growth-oriented enterprises. A well-functioning entrepreneurship ecosystem includes six pillars: skilled human capital,well-functioning markets, an encouraging policy environment, availability of financing, anentrepreneurship-friendly culture, and supportive entrepreneurship organizations and networks. This policy note responds to a request from the government to assess the current state of Cambodia’s entrepreneurship ecosystem and to identify deficiencies that are holding back the success of domestic enterprises. The note assesses Cambodia’s performance across the six pillars of the entrepreneurship ecosystem. Given the important role that innovation plays in entrepreneurial outcomes, this note also includes a brief analysis of Cambodia’s national innovation system. The note provides recommendations for how the Cambodian government can use policy to create amore robust system of support for these domestic enterprises and the entrepreneurs who establishand manage them. Given Cambodia’s struggle with the missing middle of enterprises, this note focuses particularly on policies to encourage thetypes of dynamic small- and medium-enterprises (SMEs) that grow quickly and can have a potentially transformational effect on the economy. To provide some useful lessons on improving support for entrepreneurship, the note also includes international examples from countries, such as Singapore and Malaysia, that started with a similar profile of FDI-led development and, over time, have successfully putin place the conditions necessary to nurture and grow a dynamic domestic private sector.